Attitudes of medical students towards primary care specialty: a cross-sectional survey in a public university - Jahn Kassim, Puteri Shanaz; Keng Yap, Ng; MZ, Nik Nur Qabila; F H, Muhammad; A, Hanifatiyah; Jamani, Nurjasmine Aida (Academy of Family Physicians of Malaysia, 2019)
The importance of primary care in Malaysia has increased due to the growing morbidity and mortality for preventable diseases. Ministry of Health has recently called for more trained family medicine specialists to serve at primary care clinics nationwide. However, fewer graduates intend to become primary care physicians. The objective of this study is to explore the attitudes of medical students towards primary care specialty.